How to use (and not to use) movement‐based indices for quantifying foraging behaviour. Issue 4 (18th December 2017) - Halperin, Topaz; Kalyuzhny, Michael; Hawlena, Dror
Abstract: Movement‐based indices such as moves per minute (MPM) and proportion time moving (PTM) are common methodologies to quantify foraging behaviour. We explore fundamental drawbacks of these indices that question the ways scientists have been using them and propose new solutions. To do so, we combined analytical and simulation models with lizards foraging data at the individual and species levels. We found that the maximal value of MPM is constrained by the minimal durations of moves and stops. As a result, foragers that rarely move and those that rarely stop are bounded to similar low MPM values. This implies that (1) MPM has very little meaning when used alone, (2) MPM and PTM are interdependent, and (3) certain areas in the MPM‐PTM plane cannot be occupied. We also found that MPM suffers from inaccuracy and imprecision. We introduced a new bias correction formula for already published MPM data, and a novel index of changes per minute (CPM) that uses the frequency of changes between move and stop bouts. CPM is very similar to MPM, but does not suffer from bias. Finally, we suggested a new foraging plane of average move and average stop durations. We hope that our guidelines of how to use (and not to use) movement‐based indices will add rigor to the study of animals' foraging behaviour.